The influence of relationships and alcohol use by adolescents - Benincasa, Miria; Tavares, Ana Luiza; Barbosa, Vivian Miucha Moura; Lajara, Mayara de Paula; Rezende, Manuel Morgado; Heleno, Maria Geralda Viana; Custódio, Eda Marconi (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2018)
Alcohol is a substance that is increasingly present in adolescent consumption. The present study aimed to describe the use of alcohol and the quality of social relations between family and friends to identify how they influence alcohol consumption. It is a cross-sectional study, whose data were collected with a sample of 2423 students, enrolled in High School. The data expresses the significant presence of alcohol in the relationships and the use link with both family and social relationships of peers, regardless of the quality perceived in these relationships. The data are relevant for thinking about the effectiveness of public policy interventions considering family and social ties.